¿Cuáles son las nuevas competencias blandas que las empresas de América Latina deben desarrollar en sus colaboradores para responder a la nueva realidad causada por la pandemia del Covid-19? (2021)
The purpose of this document is to compile a compilation of Soft Skills in Latin America from 2010 to 2021 and also to learn about a new training model known as “Reskilling” that arises in the Covid-19 pandemic as an alternative or Necessity for companies due to drastic changes in their business models, in the work modality whether teleworking or home office, the change or substitution of jobs and in some cases the change of functions in the same job, added to this the necessary use of technological tools as a means to develop.